2015
DOI: 10.1515/auoc-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine contaminants (PCBs, DDTs, HCB & HBDE) in fish from the Lake Varna and Lake Beloslav, Bulgaria

Abstract: Abstract.Concentrations of organochlorine compounds such as polychlorinated biphenyls (PCBs), DDT and its metabolites, hexachlorobenzene (HCB) and hexachlorobutadiene (HBDE) were determined in three fish species: goby (Neogobius melanostomus), golden grey mullet (Mugil auratus) and silverside (Atherina boyeri). Samples were collected from the Lake Varna and the Lake Beloslav in 2014. The edible fish tissues were analyzed in order to investigate the presence of pollutants in species from the lakes near Varna Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Rapid industrial and economic development has occurred around the lakes over the past few decades, leading to anthropogenic contamination of the aquatic environment. Several studies have confirmed the water quality of the lakes and some pollutants, [25][26][27] but to our knowledge studies on the bioaccumulation of metals in fishes from Lake Burgas and Mandra lake are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid industrial and economic development has occurred around the lakes over the past few decades, leading to anthropogenic contamination of the aquatic environment. Several studies have confirmed the water quality of the lakes and some pollutants, [25][26][27] but to our knowledge studies on the bioaccumulation of metals in fishes from Lake Burgas and Mandra lake are scarce.…”
Section: Introductionmentioning
confidence: 99%